Proposisi dalam Rubrik “Akhbār Indūnīsyā” pada Situs al-jazeera.net Edisi Februari 2025 (Studi Tata Bahasa Kasus): Proposisi dalam “Akhbār Indūnīsyā” Rubrik al-jazeera.net Edisi Februari 2025 (Studi Tata Bahasa Kasus) - Kusuma, Dwiki; Komarudin, Edi; Dayudin, Dayudin (Language Development Center, 2025)
Background: Arabic news texts have many complex sentences, and the identity of the agent or subject of the sentence is frequently withheld. In addition, the study of case grammar on Arabic news is still relatively minimal and rarely discussed by many people. Purpose: This study aims to identify and describe deeply the propositional case and the classification of verbs as propositional elements in the news text in the rubric “Akhbār Indūnīsyā”. Method: This research uses analytic descriptive method with a case grammar approach. The data source in this research is the rubric “Akhbār Indūnīsyā” on al-jazeera.net website. The techniques used in this research are reading, note taking, purposive sampling, and PUP (pilah unsur penentu) techniques. Results and Discussion: The results show that there are 10 data about propositions contained in the rubric “Akhbār Indūnīsyā” with various propositional cases and verbs classification. Conclusions and Implications: Based on this research results, it was found: (1) 10 propositional cases, namely agentive cases, experiencer cases, instrumental cases, benefactive cases, objective cases, locative cases, source cases, goal cases, time cases, and comitative cases; and (2) 3 verbs classifications, namely state verbs, process verbs, and action verbs. The findings of this research strengthen the relevance of case grammar theory in analyzing the logical structure (semantic structure) of complex sentences. The application of propositional case roles such as agentive, experiencer, benefactive, objective, and location in nouns and case frames in verbs proved effective in revealing meaning relationships in Arabic news texts. This indicates that case grammar theory has cross-linguistic flexibility and can be applied to Semitic languages including Arabic. Understanding the semantic roles in sentences can help Arabic learners interpret texts more critically, especially in journalistic literature that are rich in information construction. In addition, language practitioners such as translators, journalists, and teachers can utilize this approach to deepen their understanding of implicit meanings in news texts. In addition, this research offers room for more extensive further research, such as the application of case grammar theory to non-news texts such as literary texts, religious texts, or academic texts in Arabic.